2017
DOI: 10.1080/09593985.2017.1307889
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of depression and medications on incidence of falls among people with late effects of polio

Abstract: The purpose of this study was to determine if falls in polio survivors, with or without post-polio syndrome (PPS), are related to number of medications taken, use of anti-depressant or psychoactive medications, or self-report of depression. A survey was sent to 300 members of a regional polio support group, asking them to document their fall history, medications used, and the presence of depression. Depression was measured by self-report and with the Geriatric Depression Scale, short form (GDS-15). One hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Seventy-five percent of the patients reported that they had fallen at least once in the past year, which is similar to the results of previous studies on falls in patients with prior polio (5,9). Other studies (6,8,(10)(11)(12)(13) have reported a fall rate of 59-69% in the same patient group. Regarding falls during the past year, people with prior polio have more than twice as many falls as the general population, 65 years of age and older (14).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Seventy-five percent of the patients reported that they had fallen at least once in the past year, which is similar to the results of previous studies on falls in patients with prior polio (5,9). Other studies (6,8,(10)(11)(12)(13) have reported a fall rate of 59-69% in the same patient group. Regarding falls during the past year, people with prior polio have more than twice as many falls as the general population, 65 years of age and older (14).…”
Section: Discussionsupporting
confidence: 86%
“…Many patients with prior polio have muscle weakness in the lower extremities (1), which limits their movements and has been shown to be directly related to falls (4)(5)(6). Patients with prior polio often have a decreased balance and walking speed compared with healthy controls of the same age (7), they are known to have a fear of falling (5,6,(8)(9) and have been reported to fall often (5,6,(8)(9)(10)(11)(12)(13). It is important to identify the circumstances and consequences of falls in patients with prior polio, in order to prevent falls and fear of falling, and to analyse the necessity of interventions to prevent falling.…”
Section: Division Of Rehabilitation Medicine Danderyd University Hosmentioning
confidence: 99%
“…Regarding the association between antipsychotic medication and risk of hip fracture, Wu et al’s (2015) cohort study focused on antipsychotic medication, and demonstrated elevated hip fracture risk among schizophrenic subjects who had received such drugs [21]. Not all research findings have been consistent, however; for example, a study conducted to determine the association between anti-depressant medication and the incidence of falls among people with late-onset polio sequelae suggested that, while depression is related to the incidence of falls among polio survivors, fall incidence was not positively correlated with the use of anti-depressant or psychoactive medications [22]. Among the older adults, this might be not just related to Parkinson disease, but to all the neurological conditions, especially Alzheimer’s disease, that we can consider as an accelerated form of ageing including the Motor Risk Cognitive Syndrome [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported fear of falling in 60–95% of PPS patients [ 1 , 9 , 10 , 11 ]. Additional risk factors for falls in PPS patients include fatigue, muscle and joint pain, reduced sensation in the legs, depression, reduced gait performance, and impaired dynamic balance [ 1 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%